Gambaran Status Kesehatan Gigi dan Mulut Pada Perkumpulan Discjokey (Jurnal Kesehatan Siliwangi, 2020)
DESCRIPTION OF DENTAL AND ORAL HEALTH STATUS IN DISCJOKEY SOCIETIES Julitah ¹ , Tri Widyastuti ² Jurusan Keperawatan Gigi Politeknik Kesehatan Bandung ABSTRACT The health status of person’s teeth and mouth is influenced by four factors namely heredity, environment (physical, biology, social), behavior, and health services. Of four factors, behavior affects and plays an important role in direct oral and dental hygiene. The behavior of e Discjokey at night tends not to pay attention to the maintenance of healthy teeth and mouth such as brushing teeth that are less regular and often smoking ang drinking alcohol in high levels. This study aims to determine the picture of dental and oral health status in discjokey association. The type of research used is a literature study that is a picture of the health status of teeth and mouth in the discjokey association which measured in caries experience index (OHI-S, DMF-T, PTI, RTI). The results showed 15% of respondents have criteria OHI-s well, 85% criteria OHI-S moderate, in addition to the results the criteria of DMF-T showed 10% is very low, 40% low, 40% moderate, 5% higher, 5% very high. Beside that the results of 100% PTI criteria with a bad category, while for the results of the criteria of 98% RTI which is relatively high. Keywords : dental and oral health status (OHI-S, DMF-T, PTI, RTI)